2019
DOI: 10.1073/pnas.1913092116
|View full text |Cite
|
Sign up to set email alerts
|

The generation and propagation of the human alpha rhythm

Abstract: The alpha rhythm is the longest-studied brain oscillation and has been theorized to play a key role in cognition. Still, its physiology is poorly understood. In this study, we used microelectrodes and macroelectrodes in surgical epilepsy patients to measure the intracortical and thalamic generators of the alpha rhythm during quiet wakefulness. We first found that alpha in both visual and somatosensory cortex propagates from higher-order to lower-order areas. In posterior cortex, alpha propagates from higher-or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
216
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(252 citation statements)
references
References 90 publications
(110 reference statements)
28
216
4
4
Order By: Relevance
“…Based on EEG data from human participants, we demonstrated that the direction of alpha travelling waves (8-13Hz) is task-dependent, confirming suggestions from prior studies (Alamia & VanRullen, 2019;Halgren et al, 2019;Lozano-Soldevilla & VanRullen, 2019;Zhang et al, 2018), and verifying the predictions of our own modeling study on the generation and propagation of alpha oscillations (Alamia & VanRullen, 2019). Specifically, we characterized FW waves travelling from occipital to parietal regions elicited by visual stimulation, and BW waves in the reversed direction dominating during rest state.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Based on EEG data from human participants, we demonstrated that the direction of alpha travelling waves (8-13Hz) is task-dependent, confirming suggestions from prior studies (Alamia & VanRullen, 2019;Halgren et al, 2019;Lozano-Soldevilla & VanRullen, 2019;Zhang et al, 2018), and verifying the predictions of our own modeling study on the generation and propagation of alpha oscillations (Alamia & VanRullen, 2019). Specifically, we characterized FW waves travelling from occipital to parietal regions elicited by visual stimulation, and BW waves in the reversed direction dominating during rest state.…”
Section: Discussionsupporting
confidence: 88%
“…It should be emphasized that the current experimental design directly contrasted the conditions of visual processing and resting state within each trial. Previously, a number of studies had examined travelling waves under various single-task conditions, including visual stimulation (Alamia & VanRullen, 2019;Lozano-Soldevilla & VanRullen, 2019;Muller et al, 2014;Nauhaus et al, 2012), sleep (Muller et al, 2016) or quiet wakefulness (Alamia & VanRullen, 2019;Halgren et al, 2019). While these experiments confirmed the existence of travelling waves, they did not make it possible to track how the waves change from one condition to another.…”
Section: Contributions Of the Current Studymentioning
confidence: 99%
See 3 more Smart Citations